Tsunami Disaster Mitigation and Preparedness in the South Coast Area of Malang Regency - Muayyad, Ahmad; Nurwahidiah, Anisya; Maimun, Julia Amelia; Arisanty, Deasy; Juwairiyah, Juwairiyah (Universitas Lambung Mangkurat, 2025)
The Indonesian archipelago is located on the subduction tectonic plate path, the existence of the Indonesian archipelago is on the subduction tectonic plate path, the existence of this subduction process makes the Indonesian archipelago vulnerable to earthquakes of both low and high magnitude. A violent plate collision or shift accompanied by an earthquake in the ocean has the potential to cause a tsunami. The South Coast of Malang is a beach located in the south of Java Island and is one of the beaches directly facing the zubduction zone which causes a high frequency of earthquake events and can even trigger tsunamis in this area. This research aims to determine community preparedness in facing the threat of the tsunami disaster using data collection methods in the form of interviews, questionnaires, field observations and literature studies. The research results show that community preparedness in Tambakrejo Village, especially in Sendang Biru Hamlet, is still relatively low with a lack of basic community knowledge about disasters and potential disasters around them.